2012
DOI: 10.5433/1679-0359.2012v33n4p1507
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência de anticorpos anti-Neospora caninum em cães da cidade de Cuiabá, Estado de Mato Grosso

Abstract: ResumoO presente avaliou a prevalência de anticorpos anti-Neospora caninum em 406 cães da cidade de Cuiabá, Estado de Mato Grosso pela Reação de Imunofluorescência Indireta (RIFI) com ponto de corte na diluição inicial de 1:50. Foram observados 27 cães positivos (6,6%, IC95% 4,6-9,6%) com títulos variando entre 50 e 1600. Segundo a raça estudada, a maior frequência foi observada para cães Pit Bull onde 4 cães (16,7%) foram positivos (P=0,06). Não houve diferença significativa entre a soropositividade e a faixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…This exposure must have been increased Most of the dogs that were seropositive for N. caninum were also between four and nine years old; however, there was no significant association between age group and the serological results (Table 2), similar to other studies (Jesus et al, 2006;Melo et al, 2012). Seropositive males were also more prevalent than seropositive females in the 1 st and 2 nd collections, but there was no significant association, similar to other studies (Jesus et al, 2006;Melo et al, 2012;Constantino et al, 2016). In only one study, seropositive males were significantly more prevalent than seropositive females (Mascolli et al, 2015).…”
Section: Resultssupporting
confidence: 85%
“…This exposure must have been increased Most of the dogs that were seropositive for N. caninum were also between four and nine years old; however, there was no significant association between age group and the serological results (Table 2), similar to other studies (Jesus et al, 2006;Melo et al, 2012). Seropositive males were also more prevalent than seropositive females in the 1 st and 2 nd collections, but there was no significant association, similar to other studies (Jesus et al, 2006;Melo et al, 2012;Constantino et al, 2016). In only one study, seropositive males were significantly more prevalent than seropositive females (Mascolli et al, 2015).…”
Section: Resultssupporting
confidence: 85%
“…In the present study, taking into consideration the ELISA (43.1%) and IFAT (30.4%) test results, a higher frequency of antibodies against N. caninum was observed than in other studies conducted in different regions of Brazil (DANTAS et al, 2013;LANGONI et al, 2013;LOPES et al, 2011;MELO et al, 2012;MINERVINO et al, 2012;SICUPIRA et al, 2012;VALADAS et al, 2010). Additionally, no difference in the infection levels between rural and urban areas was observed, thus corroborating the findings of Valadas et al (2010).…”
Section: Discussionsupporting
confidence: 89%
“…Similar data were reported in previous studies (AGUIAR et al, 2006;CUNHA et al, 2008;FERNANDES et al, 2004;MINERVINO et al, 2012). However, Azevedo et al (2005), Bresciani et al (2007), Dantas et al (2013), Langoni et al (2013) and Melo et al (2012) did not find any correlation between age and the presence of anti-N. caninum antibodies. The IFAT results did not show any positive association with N. caninum infection, although they demonstrated that the dogs were more prone to becoming infected as they grew older.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Information about the epidemiology of neosporosis and toxoplasmosis has been reported in several places in Brazil, proving the widespread circulation of these protozoans (Acosta et al, 2016;Brasil et al, 2018;Cerqueira-Cézar et al, 2017;Langoni et al, 2014). The presence of anti-N. caninum antibodies has also been reported in different animals, including cattle and dogs, in the state of Mato Grosso (Benetti et al, 2008;Benetti et al, 2009;Boa Sorte et al, 2015;Melo et al, 2012;Rodrigues et al, 2016). In the Pantanal wetlands, equids have been found seropositive for both N. caninum and T. gondii (Borges et al, 2017).…”
Section: Introductionmentioning
confidence: 99%